Comparative Analysis of Woman’s Representation in Politics in Bosnia and Herzegovina and Republic of Croatia - Mušija, Emina; Mikac, Robert; Cesarec, Ivana (Jurnal Ilmiah Widya Sosiopolitika; Vol 4 No 2 (2022): PERSPEKTIF KELAS DAN RADIKALISMEDO - 10.24843/JIWSP.2022.v04.i02.p04, 2022)
ABSTRACT Woman’s representation in politics is an ongoing issue in Bosnia and Herzegovina and Republic of Croatia. Even though these states have sufficient laws and legal documents that regulate woman’s political participation, situation in theory is still devastating. In this paper, we gave an overview of mentioned legal framework in case studies after which we analyzed current status of woman’s representation in politics through primary method of literature review. Data was collected through primarily and secondary sources. Primarily sources were based on the qualitative research of previous work, meta-analysis and comprehensive literature reviews while secondary data was collected from official webpages from relevant election commissions from Bosnia and Herzegovina and Republic of Croatia, with emphasis on the mixed-methods approach and small-n comparison. We came to conclusion that both countries have strong legal framework for ensuring higher level of female participation but still, it’s revival in today’s political world is still missing. Finally, we connected results of elected females with Society 5.0 Key words: woman’s representation; political participation; Bosnia and Herzegovina; Republic of Croatia; Society 5.0 ABSTRAK Representasi perempuan dalam politik merupakan isu yang sedang berlangsung di Bosnia dan Herzegovina dan Republik Kroasia. Meskipun negara-negara ini memiliki undang-undang dan dokumen hukum yang memadai yang mengatur partisipasi politik perempuan, situasi secara teori masih sangat memprihatinkan. Dalam makalah ini, kami memberikan tinjauan tentang kerangka hukum tersebut dalam studi kasus, setelah itu kami menganalisis status representasi perempuan dalam politik saat ini melalui metode utama kajian pustaka. Data dikumpulkan melalui sumber primer dan sekunder. Sumber utama didasarkan pada penelitian kualitatif dari pekerjaan sebelumnya, meta-analisis dan tinjauan literatur yang komprehensif sementara data sekunder dikumpulkan dari halaman web resmi dari komisi pemilu yang relevan dari Bosnia dan Herzegovina dan Republik Kroasia, dengan penekanan pada pendekatan metode campuran dan kecil. -n perbandingan. Kami sampai pada kesimpulan bahwa kedua negara memiliki kerangka hukum yang kuat untuk memastikan tingkat partisipasi perempuan yang lebih tinggi, tetapi kebangkitannya di dunia politik saat ini masih belum ada. Terakhir, kami menghubungkan hasil perempuan terpilih dengan Society 5.0 Kata kunci: representasi perempuan; partisipasi politik; Bosnia dan Herzegovina; Republik Kroasia; Masyarakat 5.0